(3deGPG jG Cejs (3cja JJYGajf ef LQM GdCe h JLfHjf CWaGdc JhGQK GdCdes - (3GdfLGQ, SGQIs ((3GdbGgQIs (3OGQ Ohfs, 2024)
(3deGPG jG Cej Hbde O (B. (3SGQI GdfLGQ (B... (3dcpqd GHfmI JJCnqdoe hJJYnqKQ hoJMGhod GdfghnV(B.. (3dcpqd Cmqe JNnTi nJcQGQ GdJLQHI, hJSnYi dMeGjpI CHfGpFgG ef BKGpQ eGpVjngG GdCpdje, ogfG SJJenqcpfjf ef EjbGa pSrdSGd GdCndpe hoJSpqWQjnf Hbdepc bUJpc CfpJ, hnJYjTjnf GdMjGnI GdJj WGdeG nQpZHpJ ajgG HeSGYnOI ef oJMHjnfge hojMHhfpc, dJJMnqQQj hJefpMj CHfGnAc GdoMH hGdSdGne GddnPrjf JefjpJ Cf nJfnYej HgeG(B. (3aj gPG GdcJGH JLQHlI cGedlI dEOQGc GdCde hJaSjpQ CSHGpHg heYGfjg, hnage BKGpQg hfJGFLg(B. (3aqc TaQI GdJaGUjd hGdCMOGK GdJj JYGjpTjnfgG ogfG hGdBf, hoJYQpbd eSGQ MjGJc(B. (3aQUI dGSJYGOpI PGmJ bhjI hoMQI bGOQI Ydi JQHjI CHfGmA eDnqgdjnf pdnNhpV QMdI GdMjGI(B. (S0(3aj gPG GdcJGH nJYpQV OcJhQI (S0(3SGQI(S1 (3HHQGYmI TOjOmI YdGnbI GdCpqe hGHfJgG, ceG oJSGYoO gPg GdGHfnI GdJj JCnqdeJ HSHH YdGnbI oeeJnqOI oeNJdWI GdeTGYQ HoCmqe cGfJ JaJpboO GdpqUaGJ GdYGWajI GddGReI dpQYGjpI Wamd(S1(B. (3O(B.(3CMeO CHh GdhaG, GSJTGQj GdWH GdfaSj (S0(3aj SHjpd GdJYoqQpa Ydi GdCndpe GdfaSpqj GdfGpTF Yf nabpO QYGjI GdCpqe, hYhGbHg GdneQpVnqjI aj COGA GdTNUjI dGMkbG, ocpJH gPG GdcJGoH HWQjbmI aQjOmI ZjQ eSHhbmI, agfjkFG ddbGQF GdYQHpqj gPG GdcJGH heG njrMphj ef pNrHQGmJ egpfnqjmI heYdheGJ nfraSjmI ehnqKbI nJhKjkbG YdekqjG, hLOjOkI Ydi GdoCrSQpI GdYQHjpI(S1(B. (3O(B.(3CMeO YjO GSJTGQj GdWH GdfaSj zcJGH SjXoqd aj GdnqPGpcQpI dSfhGmJ pYnqOI, ojhnUi Hpg dChdFcn GdPjf JCnqdehG ef oLQM GdoCehepI(B.. (3heG RGodhG(S1s
Keywords: (3GdCeheIs